A Comparative Study of Competitive Anxiety between Basketball and Volleyball Players - Singh, Anita; Parmar, Devender Singh (International Research Journal of Management, IT & Social Sciences, 2015)
Anxiety is a psychological and physiological state characterized by somatic, emotional, cognitive and behavioral components. The root meaning of the word anxiety is `to vex or trouble. The objective of this paper is to compare the competitive anxiety between basketball and volleyball players. For this purpose 40 Male intercollegiate players from Basketball (20) and Volleyball (20) were taken as sample. For the purpose of this study the standardized Rainer Marten (SCAT, 1990) Scale was used.Â  The Questionnaire was administers in small groups during the intercollegiate Basketball and Volleyball tournament. The results of the study have revealed that there is no significant difference between the competitive anxiety of Basketball and Volleyball players of intercollegiate, as no significant difference has seen in the mean score at the Basketball and Volleyball players on competitive anxiety. Therefore it may be said that there is no influence of competitive anxiety at the Basketball and Volleyball players of inter-college level.Â